SEDIMENTATION BROKEN IN INCLINED SEOIMENTADORES - Lama-Ramirez, R. (1999)
We have studied the batch sedimentation of aqueous suspensions of precipitated calcium carbonate, barium sulfate and lead oxide settlers inclined rectangular and circular cross section. The énguio tilt with respect to the horizontal between 35 ° and 75 °, to suspensions that vary in strength between 39.4 and 1070 g / l.Las obtained apparent sedimentation velocities ranging from 0.071 to 17.6 cm / min. the apparent sedimentation rate has been correlated using a modified version of the equation of Nakamura and Kuroda (1), see above.